Diagnosis of small bowel obstruction due to Shine-Muscat grape ingestion: case report - Gu, Chunhui; Zhang, Youcheng; Jiang, Guoqing; Hu, Xiaoting (Frontiers in Pediatrics, 2024)
IntroductionThis case report describes a rare instance of small bowel obstruction (SBO) caused by the ingestion of a whole Shine-Muscat grape in a 7-month-old infant. This case adds to the scientific literature by highlighting the potential risk of common fruits, such as grapes, in causing serious gastrointestinal blockages in pediatric patients, which is an uncommon but important consideration for pediatricians and caregivers.Main symptoms and clinical findingsA 7-month-old female presented with a 3-day history of vomiting, which progressed to bilious vomiting, accompanied by abdominal distension and dehydration. Abdominal CT imaging revealed dilated small bowel loops and a spherical low-density lesion suggestive of an obstructing foreign body.Main diagnoses, therapeutic interventions, and outcomesThe diagnosis of mechanical small bowel obstruction due to a foreign body was confirmed intraoperatively. The obstructing object was identified as a whole Shine-Muscat grape. Surgical management involved a minimally invasive laparoscopic approach to crush and move the grape into the colon, avoiding bowel incision. The patient recovered well postoperatively and passed the grape fragments naturally, resuming a normal diet within days.ConclusionThis case underscores the importance of considering fruit ingestion as a potential cause of intestinal obstruction in infants. Pediatric surgeons and emergency clinicians should be aware of this rare but significant risk and employ careful history-taking, appropriate imaging, and minimally invasive techniques to manage such cases effectively.